SERVICE EXCELLENT RUMAH MAKAN PADANG DALAM PERSPEKTIF WISATA ISLAMI - Wardi, Yunia; Abror, Abror; Trinanda, Okki (International Journal of Community Service Learning, 2019)
Padang Restaurant is one of the ethnic restaurants in Indonesia from Minangkabau. The existence and "brand" of Padang Restaurant has been very well known in the territory of Indonesia and even in several neighboring countries such as Australia, Singapore, Malaysia and other countries. Padang cuisine, with its taste and variety, is currently in great demand by the wider community. Unlike the canteen, cafe or restaurant, where visitors are given a menu and order the desired food, at the Padang restaurant, when visitors sit, they will be served a whole selection of side dishes available with small plates. After serving then the customer just takes what he wants from the dish table. The problem that can then arise is the food that has been served, but not eaten by visitors. The food will be brought back and served to another table. Not infrequently the food that is still on the visitor's table is pulled back to serve at another table. In addition, food storage is also done in an open place so that visitors can come. These things will certainly bring cleanliness problems. For visitors who are very concerned about cleanliness, of course they will feel uncomfortable seeing the food that has been served at another table and then served on the table. Or see the food served brought from an open place. Service Excellence at the restaurant not only increases the company's profit but can also improve the image of the restaurant. When guests or consumers are satisfied with the service in their restaurant they will promote their satisfaction in the restaurant. Service Excellence is service to consumers to improve service in a company. Service Excellence in Restaurants is a service to consumers to provide satisfaction in the form of excellent service to the restaurant products. Excellent service is very important not only to get big profits but this service must be fulfilled by every company. To provide Service Excellence in the right restaurant, every employee must get training or training so that they are truly able to work well and professionally. A restaurant employee must be able to provide services to consumers whoever they are. Not only employees who are in front but all members of the company must also be able to provide the best service.